REASONING APPROPRIATION FOR THE USE OF LOCALIZATION OF MAGISTRAL OIL TRANSPORT TECHNOLOGIES USED BY INTERFERENCE DEVICES - Додик, Тарас Ярославович; Мельниченко, Юрій Гримиславович; Мельниченко, Гримислав Григорович; Марчук, Олексій Миколайович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The problem of releasinga section of main oil pipeline from the product during its repair was confirmed. The technology of isolation of oil pipeline was proposed. The specifications of new designed plugging device were confirmedandits sealing capacity was researched.